2009
DOI: 10.1007/s00774-009-0123-1
|View full text |Cite
|
Sign up to set email alerts
|

Teriparatide is safe and effectively increases bone biomarkers in institutionalized individuals with osteoporosis

Abstract: Institutionalized adults with severe developmental disabilities have a high rate of minimal trauma and appendicular fracture. There is little information about osteoporosis treatment in this population. In this efficacy and safety study, men and women with severe developmental disabilities and osteoporosis received 20 mcg teriparatide subcutaneously daily for 18-24 months. Markers of bone formation [procollagen type 1 intact N-terminal propeptide (P1NP)] and resorption [C-telopeptide (CTx)] were measured at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Horwitz et al (2011) indeed demonstrated extensive bone resorption with high dose PTH (4 pmol/kg/h) delivered by continuous infusion pump, resulting in hypercalcemia. Intermittent delivery increased bone turnover within low BMD patients who exhibited 2.1 fold increased bone formation, and 2.7 fold increased bone resorption (Ryder et al, 2010). Nakamura et al (2012) also demonstrated increased BMD (2.3 to 6 fold) within vertebral fracture patients following intermittent administration (56.5 μg/week).…”
Section: Pthmentioning
confidence: 87%
See 1 more Smart Citation
“…Horwitz et al (2011) indeed demonstrated extensive bone resorption with high dose PTH (4 pmol/kg/h) delivered by continuous infusion pump, resulting in hypercalcemia. Intermittent delivery increased bone turnover within low BMD patients who exhibited 2.1 fold increased bone formation, and 2.7 fold increased bone resorption (Ryder et al, 2010). Nakamura et al (2012) also demonstrated increased BMD (2.3 to 6 fold) within vertebral fracture patients following intermittent administration (56.5 μg/week).…”
Section: Pthmentioning
confidence: 87%
“…PTH has been administered in humans for many years investigating its efficacy for bone formation within healthy adults (Horwitz et al, 2011), adults with low BMD (Ryder et al, 2010), postmenopausal women (Schafer et al, 2013), mandibular defects (Kwon et al, 2012) and vertebral fractures (Supplementary Table 5). Continuous delivery has been shown to reduce bone formation markers and increase bone resorption.…”
Section: Pthmentioning
confidence: 99%
“…Its synthesis is stimulated by 1,25-dihydroxyvitamin D. OC contains three glutamic acid residues, which are converted to gamma-carboxyglutamate (gla) by vitamin K-dependent post-translational carboxylation. 2,17 The carboxylation process leads to a conformational change in protein which allows the binding of OC with hydroxyapatite and mineralization in the bone matrix. There are also non-carboxylated or undercarboxylated forms of OC released into the circulation, 24 but its significance in postmenopausal osteoporosis fracture prediction is less than intact OC.…”
Section: Bone Formationmentioning
confidence: 99%
“…16 Procollagen peptide concentrations are reduced by antiresorptive treatments (such as oestrogen and bisphosphonates) and are increased by the anabolic agents such as teriparatide (human recombinant parathyroid hormone). 17,18 Bone-specific alkaline phosphatase. Alkaline phosphatase (ALP) is a membrane-bound enzyme and is present in almost all body tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Its use has been approved by the US Food and Drug Administration (FDA) only for adults (1). Contraindications to the use of teriparatide include the following: any hypercalcemic disorder, osteosarcoma, metastatic bone disease, Paget's disease of bone, pregnancy, and radiation therapy to the skeleton or to soft tissue in which a skeletal port is exposed.…”
Section: To the Editormentioning
confidence: 99%